2013
DOI: 10.4236/abcr.2013.24019
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at <i> GSTM </i>1, <i> GSTP </i>1, <i> GSTT </i>1 Detoxification Genes Loci and Risk of Breast Cancer in Kazakhstan Population

Abstract: Associations of null polymorphism (copy number variation) of detoxification genes GSTM1, GSTT1 and GSTP1 (at rs2495636, 105 Ile/Val) with the breast cancer (BC) were assessed in two main ethnic groups of the Republic of Kazakhstan (Kazakhs and Russians). Total number of patients was 181, and of controls 397. Statistically significant difference was observed between BC patients and healthy individuals in alleles frequency (χ 2 = 4.89, р = 0.007) of GSTP1 gene at rs2495636 (105 Ile/Val) among the Kazakhs ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This finding is similar to the Yogyakarta, Indonesian, 10 Khazakstan, 16 Chinese, 7 Taiwanese, 17 Brazilian, 18 and Italian. 19 But in Malay subjects from our http://mji.ui.ac.id data showed a significant deviated from HardyWeinberg equilibrium.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is similar to the Yogyakarta, Indonesian, 10 Khazakstan, 16 Chinese, 7 Taiwanese, 17 Brazilian, 18 and Italian. 19 But in Malay subjects from our http://mji.ui.ac.id data showed a significant deviated from HardyWeinberg equilibrium.…”
Section: Discussionsupporting
confidence: 84%
“…SNPs CYP2E1 −1293G>C/−1053C>T (rs3813867/rs2031920), NQO1 609C>T (rs1800566), and MPO −463G>A (rs2333227) were investigated by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis using the Hinf I, Rsa I, and Aci I restriction enzymes, respectively [ 19 , 30 , 31 ]. Deletions of GSTT1 and GSTM1 were investigated by multiplex PCR, and the β -globin gene ( HBB ) was used as an internal reaction control [ 22 ]. β S globin gene cluster haplotypes were investigated by PCR-RFLP and talassemia α 2 del 3.7kb by PCR [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that individuals with low NQO1 activity and high CYP2E1 activity would potentially be more susceptible to the toxic effects of xenobiotic than those with low CYP2E1 and high NQO1 activities [ 21 ]. GST(M1/T1) is involved in the detoxification of a wide variety of potentially toxic and carcinogenic electrophiles by conjugating them to glutathione [ 22 ] and enhancing xenobiotic solubility which facilitates its elimination [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also discussed as a founder mutation for the development of BC in Uzbek, Ashkenazi Jewish, Tatar and Russian populations [43][44][45][46]. Previous studies of the BRCA1 gene showed the absence of the c.5266dup PV in a cohort of 121 Kazakh patients with BC, mean age of 50.3 ± 11.5 years [47]. A previous study using Sanger sequencing to identify BRCA variants in sporadic BC women from Kazakhstan with an average age of 50-51 years did not reveal any recurrent PVs, including BRCA1 c.5266dup and c.5278-2del [48].…”
Section: Recurrent and Founder Pathogenic Variantsmentioning
confidence: 99%